(TiO2(B) Nanosheet)/(Metallic Phase MoS2) Hybrid Nanostructures: An Efficient Catalyst for Photocatalytic Hydrogen Evolution. Issue 12 (5th September 2019) - Wang, Jing; Jia, Henglei; Guo, Yingjie; Zhang, Yanpei; Xie, Qindong; Zhu, Houyu; Sun, Jie; Shi, Feng; Liu, Zong-Huai; Jiang, Ruibin
Abstract : Developing photocatalysts that can efficiently produce hydrogen from water under solar irradiation is highly desired for sustainable and clean hydrogen energy. Herein, it is demonstrated that (TiO2 (B) nanosheet)/(metallic phase MoS2 ) hybrid nanostructures have high activity for photocatalytic hydrogen evolution from water. The TiO2 (B) nanosheets are prepared by solvothermal reaction with TiCl3 as a precursor in the presence of ethylene glycol. Due to the short transportation distance of charge carriers, more negative conduction band edge, and the existence of oxygen vacancy, the photocatalytic activity of the pure TiO2 (B) nanosheets is one order of the magnitude larger than that of the commercial P25. After loading metallic phase MoS2, the photocatalytic activity of TiO2 (B) is further improved by ≈13 times to 1444 μmol g −1  h −1 because of the superior activity of metallic phase MoS2 for hydrogen evolution. The findings provide a cost‐effective and highly active photocatalyst for hydrogen production from water and are very helpful for the development of sustainable and clean hydrogen energy. Abstract : (TiO2 (B) nanosheet)/(metallic phase MoS2 ) hybrid nanostructures are prepared and exhibit high photocatalytic activity toward hydrogen evolution. The photocatalytic activity of the prepared TiO2 (B) nanosheets toward hydrogen evolution is one order of magnitude higher than that of the commercial P25. After hybridization with metallic phase MoS2, the photocatalytic activity is further elevated by ≈13 times.